Developing Anti-Racist Scholars: The Role of Adult Education Graduate Programs - Barbara A. Metelsky; Thomas R. Easley (Adult Education Research Conference, 2009)
The purpose of this paper and this roundtable is to explore the role of adult education graduate programs in preparing anti-racist scholars. In dialogue with others, we seek to understand the broad roles that programs have and the specific responsibilities that adult education graduate students, faculty members, and program administrators may undertake toward this end.